PELAKSANAAN PILAR PENINGKATAN EKONOMI RAKYAT DI KECAMATAN TAPUNG KABUPATEN KAMPAR TAHUN 2012-2013 - Sejahtra, Kurnia; ", Ishak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Program improve people's economy is one of the pillars of the five pillars of development designed by Kampar Kampar regent governed by Kampar District Regulation No. 12 of 2012 on the Medium Term Development Plan (RPJMD ) Kampar . Improve people's economic pillar aims to create a society that is developing the potential of natural resources and community resources to build a solid democratic economy . However, the implementation of the pillars of improving people's economy has not done well and have not been able to change the economy of the community in its implementation in the district of Kampar Regency Tapung 2012-2013 .This study was conducted to determine the causal factors and constraints why pillars improve people's economic program can not alter the economy of the community in its implementation in the district of Kampar subdistrictTapung 2012-2013 . The location study was conducted in the District Tapung Kampar regency . Penlitian type is qualitative research with descriptive method.The results showed that the implementation of the pillars of economic improvement of the people in the district of Kampar Regency Tapung years 2012-2013 has not done well and have not been able to change the community's economy . Some contributing factor is the factor of communication , resource factors , factors disposition , and factor structure of the bureaucracy . Some obstacles are programs , program implementers and program beneficiaries.Keywords : Policy Implementation , Economic Improvement of the People